Perkembangan Kemampuan Belajar Passing Sepak Bola menggunakan Pola Game Pass and Move Kelas VII G SMP Negeri 11 Surabaya - Moch Abdul Muis; Bambang Ferianto; Tjahyo Kuntjoro (Journal of Creative Student Research, 2024)
The problem formulation of this research is what efforts are made to improve the learning outcomes of passing in football through games and moves. The aim of this research is to determine the increase in the results of learning patterns of passing through the pass and move game at SMPN 11 Surabaya. Descriptive methods were used in this research in the form of Classroom Action Research (PTK). The sample from this research was 32 students at SMPN 11 Surabaya. The assessment of the data analysis mechanism applies the results of the percentage of completeness. The analysis results show that the lowest pre-cycle value is 44.83, the highest value is 72.34 and the average value is 60.36. In cycle 1, the lowest score was 59.28, the highest score was 85.17 and the average score was 72.44. In cycle 2 the lowest value was 62.97, the highest value was 88.88, and the average value was 76.06. The student score in the pre-cycle was 0%, cycle 1 was 34.37% with 11 students and cycle 2 was 53.17% with 18 students. Based on the analysis, you will get the results of the inner leg passing technique using group learning for students at SMPN 11 Surabaya.